A study of serum-ionized calcium in neonates with unconjugated hyperbilirubinemia on phototherapy - Pal, Swasti; Kalra, Braham Prakash; Kalra, Vinita (Indian Journal of Child Health, 2018)
Objectives: The objective is to study the occurrence of phototherapy-induced hypocalcemia in neonates with unconjugated hyperbilirubinemia and to compare the occurrence between pre-term and full-term neonates. Materials and Methods: The study was conducted in the Neonatology Unit of Department of Pediatrics, at a tertiary care teaching hospital for 12 months. A total of 230 full-term and pre-term neonates with jaundice were recruited. Of 230 neonates, 150 were given phototherapy (cases), while 80 did not receive phototherapy and were used as control. Serum-ionized calcium levels were measured at initiation, after 24 h and after 48 h, or at the end of phototherapy in the case duration of phototherapy was <48 h. Serum-ionized calcium was repeated at 24 h after the completion of phototherapy. In the control group, ionized calcium levels were measured at the time of development of jaundice and 24 h after the initial measurement. Results: Of 150 cases who received phototherapy, 105 were term and 45 were preterm. 69 babies (46%) developed hypocalcemia after 24 h of phototherapy. Of these, 28 (40.5%) were preterm and 41 were term (59.5%). 4 patients developed symptoms, which included jitteriness and seizures. 62.2% of the total pre-term and 39% of term neonates developed hypocalcemia after phototherapy. Conclusion: This study suggests that neonates exposed to phototherapy are at the risk of developing hypocalcemia. There is a significant decline in the ionized calcium levels after exposure to phototherapy, and this level can even fall to hypocalcemic levels. As the duration of phototherapy increases, the serum levels of calcium may decline further. The risk of developing hypocalcemia is higher in pre-term neonates.